(3KQhI GdeYQaI (B:s (3QCS GdeGd GdacQj h eDSSI GdbQf GdMGOj h GdYTQjf (B/s - (3SJjhGQJ, JheGS(B.(3Cs ((3GdbGgQI(B: s (3GdOGQ GdOhdjI ddGSJKeGQGJ GdKbGajI(B, s, 2004)
(3QcGFR GdGbJUGO GdeYQaj h eGPG JaYd GdTQcGJ h deGPG JhLO h GdeDSSI GdGdcJQhfjI GVGaI Gdi GSJQGJjLjI dQGS GdeGd GdacQj(B: (3JTZjd GdeYQaI HUhQI GcHQ h GPci h GSQY(B, (3GdMLL GdeVGOI dGOGQI GdeYQaI h cPG YQV LOjO (B: (3HjY GdefJLGJ GdeYQajI (B, (3GOGQI eTQhYGJ GdeYQaI h JUeje LOjO(B: (3GdYedjGJ GdOGYeI ddJcfhdhLjG h YedjGJ eYQajI OGYeI(B, (3KbGaI LOjOI(B: (3GcJSGH efXhQ eYQaj(B, (3GVGaI Gdi GdQSeGdi GdHTQj(B, (3eHGOF GdeMGSHI ZjQ GdeJYGQa YdjgG (B, (3GdeMGSHI GdGOGQjI aj YUQ GdeYdheGJs
Keywords: (3GdeYQaIs; (3KhQI GdeYQaIs; (3QGS GdeGd GdacQjs